2014
DOI: 10.2478/folmed-2014-0014
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal Atrial Fibrillation: Dynamics of The Main Antioxidant Enzymes - Superoxide Dismutase and Catalase

Abstract: INTRODUCTION:Researchers have a particularly strong interest in the mechanisms implicated in the clinical manifestation of atrial fi brillation. OBJECTIVE: To examine dynamically the activity of the antioxidant enzymes, superoxide dismutase and catalase in patients with paroxysmal atrial fi brillation (duration < 48 hours). MATERIALS AND METHODS: The studied parameters were examined in the erythrocytes of 51 patients (59.84 ± 1.60, 26 men) immediately after their hospitalization, at 24 hours and 28 days after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(13 reference statements)
0
2
1
Order By: Relevance
“…Postoperative AF has been reported to occur in 15-50% of patients with cardiac surgery [23, 24] and 10-42% with thoracic surgery [25,26], suggesting that these two specific cohorts might have a higher incidence of AF compared with the general ICU population. The incidence range in our study (12.6%) is higher than previously thought (4-9%) [27], possibly due to the aging population and the development of more complex medical comorbidities.…”
Section: Discussioncontrasting
confidence: 71%
“…Postoperative AF has been reported to occur in 15-50% of patients with cardiac surgery [23, 24] and 10-42% with thoracic surgery [25,26], suggesting that these two specific cohorts might have a higher incidence of AF compared with the general ICU population. The incidence range in our study (12.6%) is higher than previously thought (4-9%) [27], possibly due to the aging population and the development of more complex medical comorbidities.…”
Section: Discussioncontrasting
confidence: 71%
“…In another study, paroxysmal atrial fibrillation was characterized by significantly increased activity in SOD and CAT, therefore changes in oxidative status are closely correlated to CVD (39). Increased oxidative stress in human end-stage HF may lead to specific rearrangement of catalase gene expression as a compensatory mechanism (41). In a previous study, no differences were seen in terms of superoxide dismutase activity, although glutathione peroxidase activity was lower in the atrial fibrillation (AF) group (42).…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, this difference was maintained 24 h after rhythm regularization and, even 24 days after the restoration of sinus rhythm, the activity of catalase remained increased. 53 In the same way, the study by Michałek et al reported that serum CuZn-SOD activity and serum total antioxidant capacity were significantly lower in their study groups compared to in control animals; specifically, they found that catalase activity was significantly higher and plasma GPx activity was significantly lower in dogs with chronic heart failure and AF compared to those with chronic heart failure only, sinus rhythm, or control dogs. 54…”
Section: Superoxide Dismutase and Catalasementioning
confidence: 83%